2020
DOI: 10.1002/bse.2687
|View full text |Cite
|
Sign up to set email alerts
|

Internal green integration and environmental performance: The predictive power of proactive environmental strategy, greening the supplier, and environmental collaboration with the supplier

Abstract: The effect of proactive environmental strategies (PES) on corporate performance has been debated extensively among academics; however, the significance of the pathway of those strategies—internal green integration (IGI) through greening the supplier (GTS) and environmental collaboration with suppliers (ECS)—remains undecided. This study examines environmental performance (EP) through GTS, IGI, and ECS. It also examines the direct link between PES and IGI. A conceptual framework was designed following a rigorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 97 publications
(125 citation statements)
references
References 72 publications
3
121
0
1
Order By: Relevance
“…Past studies that published by Business Strategy and the Environment Journal such as (Awan et al, 2021; Liu & Kong, 2021; Martínez Hernández et al, 2021; Shah & Soomro, 2021; Yang et al, 2019) found and claimed that green business strategies that cover leveraging of green innovation practices and green entrepreneurship mindset are the most prominent driver supporting and maintaining EP. The findings of this study have significant implications for modern business strategies from three‐points of view namely ecological, societal, and economic perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies that published by Business Strategy and the Environment Journal such as (Awan et al, 2021; Liu & Kong, 2021; Martínez Hernández et al, 2021; Shah & Soomro, 2021; Yang et al, 2019) found and claimed that green business strategies that cover leveraging of green innovation practices and green entrepreneurship mindset are the most prominent driver supporting and maintaining EP. The findings of this study have significant implications for modern business strategies from three‐points of view namely ecological, societal, and economic perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have acknowledged that organisations that have already adopted environmental strategies and sustainable policies into their processes would be able to deliver green products . Shah and Soomro (2021) found that proactive environmental strategies increase internal green integration for environmental performance.…”
Section: Sustainable Environment Practices (Env)mentioning
confidence: 99%
“…Shah and Soomro (2021) found that proactive environmental strategies increase internal green integration for environmental performance. Recent research has also suggested that environmental readiness enhances corporate innovation and competitive advantage (Zhang et al, 2020).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, organizations must be prepared to help overcome environmental problems by establishing the ability to access environmental issues regarding products, technologies, and regulations and to examine environmental issues too (Shah & Soomro, 2021). In other words, green product innovation gives businesses the chance to be pioneers, enabling them to stand out and achieve a competitive edge (Bhatia, 2021).…”
Section: Discussionmentioning
confidence: 99%